Circulating Microparticles Decrease After Cardiac Stress in Patients With Significant Coronary Artery Stenosis. Issue 10 (13th July 2016) - Sinning, Jan‐Malte; Jansen, Felix; Hammerstingl, Christoph; Meier, Arne; Losch, Jan; Rohwer, Katharina; Schmitz, Theresa; Paul, Kathrin; Sedaghat, Alexander; Schueler, Robert; Vasa‐Nicotera, Mariuca; Müller, Cornelius; et al.
ABSTRACT: Background: Cardiac stress leads to a dynamic increase of circulating microparticles (MPs) in healthy individuals that is diminished in individuals with vascular disease. The impact of coronary ischemia on circulating MP level is unknown. This study investigates the kinetics of circulating MPs during cardiac stress in patients with coronary artery stenosis. Hypothesis: Patients with significant coronary stenosis show altered circulating MP levels after cardiac stress. Methods: Eighty patients with stable coronary artery disease underwent dobutamine stress echocardiography (DSE) on the day before coronary angiography. Before, immediately after, at 4 hours, and at 24 hours after DSE, blood was drawn to determine CD144 + endothelial microparticles (EMPs), CD14 + CD16 + monocyte‐derived microparticles (MMPs), and CD31 + CD42b + platelet microparticles. A significant stenosis was defined as stenosis diameter ≥70% in a major native epicardial coronary artery with a diameter of ≥2.5 mm. Results: Significant coronary artery stenoses were found in 41 patients. In these patients, CD144 + ‐EMP and CD14 + CD16 + ‐MMP concentrations decreased immediately after DSE. Stimulation of target endothelial cells with sera from patients with significant coronary artery stenoses significantly augmented endothelial capacity to take up EMPs, but not MMPs, in vitro. Serum‐induced enhancement of endothelial phosphatidylserine receptor expression was found as a potential mechanism of increased endothelial EMP uptake and subsequently reduced circulating EMP levels after cardiac stress. Conclusions: Cardiac ischemia leads to reduced circulating MP levels under cardiac stress. Changes of endothelial MP uptake capacities could be one possible mechanism.